Wages and Productivity Growth in a Dynamic Oligopoly - Helmut Bester; Chrysovalantou Milliou; Emmanuel Petrakis (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2009)
This paper studies the innovation dynamics of an oligopolistic industry. The firms compete not only in the output market but also by engaging in productivity enhancing innovations to reduce labor costs. Rent sharing may generate productivity dependent wage differentials. Productivity growth creates intertemporal spill-over effects, which affect the incentives for innovation at subsequent dates. Over time the industry equilibrium approaches a steady state. The paper characterizes the evolution of the industry's innovation behavior and its market structure on the adjustment path.
urn:nbn:de:bvb:19-epub-13267-2
Keywords: D24; D42; D92; J31; 330; innovation; laborproductivity; oligopoly; wagedifferentials; productivitygrowth; industrydynamics; Oligopol; Innovationswettbewerb; Investition; Arbeitsproduktivität; Arbeitskosten; Dynamisches Modell; Theorie